Reproductive diapause in males of the linden bug, Pyrrhocoris apterus - Hejníková, Markéta (Jihočeská univerzita, 2022)
This thesis focuses on the male reproductive diapause in the linden bug, Pyrrhocoris apterus. We examined in detail the response of males to changing photoperiodic conditions, the change in levels of juvenile hormone, and its role in male diapause, as well as the effect of low temperature on diapause termination. We compared the physiology of males and females and pointed out important sexual dimorphism in the control of diapause. Finally, we analyzed a completely novel insect neuropeptide to and explored its possible link in the chain of control of reproductive diapause.
Reproductive diapause in males of the linden bug, Pyrrhocoris apterus
Keywords: Reproductive diapause; juvenile hormone; males; Methoprene-tolerant; Taiman; Corpus allatum; accessory glands; fertility; Reproductive diapause; juvenile hormone; males; Methoprene-tolerant; Taiman; Corpus allatum; accessory glands; fertility